PERLINDUNGAN HUKUM BAGI PEMEGANG HAK CIPTA FILM DARI KEGIATAN STREAMING DAN DOWNLOAD PADA WEBSITE ILEGAL - Hendrianto Hendrianto; Zulfikar Jaya Kusuma; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Illegal movie download activities can be detrimental to a film copyright holder because users candownload movies without having to ask permission and pay as they would if they were to watch a movie in acinema. Such activities certainly can reduce the creativity and spirit of the creation of filmmakers andhinder the development of the creative economy, which currently plays an important role for the country'seconomy and has contributed Rp. 104.4 Trillion or an average of 4.75% of GNP (Gross National Product )As a result of the widespread download and streaming of movies on illegal websites, the government hassuffered losses of more or less found the figure of 4 (four) Trillion Rupiah because the films circulating onillegal websites are not taxed.The type of research used in this study is normative juridical, namely research conducted or aimedat written legislation and forms of official documents, also called (secondary data).From the results of the study, the authors concluded that the legal consequences of copyrightinfringement from downloading and streaming movies on illegal websites as stipulated in Article 99 of LawNumber 28 of 2014 concerning Copyright, by a creator or holder of copyright / related rights, are civilized.entitled to claim compensation for copyright infringement. Whereas viewed from the criminal aspect in theCopyright Act there are several criminal sanctions in the form of imprisonment for a maximum of (4) yearsand / or criminal penalties of no more than Rp1,000,000,000.00 (one billion rupiah). Law No. 11 of 2008concerning Electronic Information and Transactions also contributes criminal sanctions to violators with amaximum imprisonment of 8 (eight) years and / or a fine of a maximum of Rp. 2,000,000,000.00 (two billionrupiah). Second, legal protection of the moral rights and economic rights of the creator needs to beimproved considering the increasing number of piracy carried out by illegal film websites. A film copyrightholder has a personal intellectual property and gives him the right to explore the economic rights of hiscreation.Keywords : Legal Protection - Copyright Streaming Films Download Movies - Illegal Website